Meningkatkan Aktivitas, Karakter Disiplin, Dan Hasil Belajar Menggunakan Model Prestasi Pada Peserta Didik Kelas Iv SDN Kelayan Selatan 9 - Nurhayda, Nurhayda; Jannah, Fathul; Agusta, Akhmad Riandy; Sari, Raihanah (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The issue with this discovery is the lack of engagement, lack of discipline, and subpar learning outcomes in PPKn education. Attempts to address these issues through the utilization of the PERSASI paradigm. The aim is to describe and analyze activity, character of discipline, and learning outcomes. The type of research used PTK. The subject of the discovery was grade IV students of SDN Kelayan Selatan 9 as many as 4 meetings. This research was conducted in 4 meetings. The research was carried out over the course of four meetings. The findings data were analyzed using descriptive analytic approaches, which involved presenting the data through tables, graphs, and interpretations using percentages. The findings indicated a progressive improvement in teacher engagement during each meeting, ultimately reaching the "Very Good" level. The level of student engagement progressively rose at each meeting, culminating in the final meeting where it reached 93% according to the criterion "Almost All Students Are Very Active". The level of discipline rose significantly during the last meeting, reaching 89% under the category "Almost All Students Are Very Disciplined". The classical learning outcomes achieved in the last meeting were 93%.